Mitigation of polycyclic aromatic hydrocarbons (PAHs) in roasted beef patties by cold plasma treatment and products quality evaluation - Yuke Hou; Yangjian Hu; Min Li; Jiahui Nong; Fengyuan Xie; Yuhan Fan; Jianhao Zhang; Xianming Zeng; Minyi Han; Xinglian Xu; Xia Wang (Food Science and Human Wellness)
The cold plasma (CP) technique was applied to alleviate the contamination of polycyclic aromatic hydrocarbon (PAH) in this investigation. Two different CP treatments methods were implemented in the production of beef patties, to investigate their inhibition and degradation capacity on PAHs. With 5 different cooking oils and fats addition, the inhibition mechanism of in-package cold plasma (ICP) pretreatment was explored from the aspect of raw patties fatty acids composition variation. The results of principal component analysis showed that the first two principal components accounted for more than 80% of the total variation in the original data, indicating that the content of saturated fatty acids was significantly positively correlated with the formation of PAHs. ICP pretreatment inhibited the formation of PAHs by changing the composition of fatty acids, which showed that the total amount of polyunsaturated fatty acids decreased and the total amount of monounsaturated fatty acids increased. Sensory discrimination tests demonstrated there were discernable differences between 2 CP treated samples and the controls, utilization of the ICP pretreatment in meat products processing was expected to achieve satisfying eating quality. In conclusion, CP treatment degraded PAHs through stepwise ring-opening oxidation in 2 reported pathways, the toxicity of PAHs contaminated products was alleviated after CP treatment.